Causal Effect Of Behavioural Competencies In Linking Emotional Intelligence And Teaching Performance In Higher Education - Habsah, Muda; Mass Hareeza, Ali; Mazuki, Jusoh (2017)
The purpose of this study was to examine the causal effect and the correlational relationship between the constructs of emotional intelligence (EI), behavioural competencies before, during, and after teaching delivery (BC-BDA-TD), as well as teaching performance (TP) in the context of public universities in Malaysia. This study answered four research questions and tested four main hypotheses. The units of analysis were academic staff from the faculty of business, management, accounting and economics that derived from the three clusters of public higher learning institutions in Malaysia. Hence, a set of self-administered questionnaire surveys were established based on the adoption and adaptation of the theories / previous studies as the instrument for data collection. Besides, multi stages of sampling procedures (stratified, cluster, and simple random) were employed as the study involved a sample size of 226 academic staff as respondents in this study. Furthermore, a statistical analysis using SPSS was employed to carry out a descriptive analysis on the demographic data. Other than that, as for inferential analysis, the Structural Equation Modelling (SEM) using AMOS was employed to answer the research questions and to test the hypotheses in this study. As a result, this study revealed that emotional intelligence (EI) had a significant and direct effect on teaching performance in the context of public universities in Malaysia. Moreover, the study had discovered that the two levels of teaching performance measured at the reaction (level 1) and learning (level 2) levels were significantly and directly influenced by an emotional intelligence of the academic staff. The findings also implied that the behavioural competencies of the academic staff before, during, and after the teaching delivery were directly influenced by the emotional intelligence of the academic staff, and further directly affected their teaching performance. Overall, these research findings supported all the hypotheses, answered the four research questions, and achieved the objectives set out in this study. With that, this study has successfully addressed the gaps found in previous studies, has contributed to the body of knowledge, as well as in providing useful implications to the public universities in Malaysia.